Proceedings of the 27th ACM International Conference on Information and Knowledge Management 2018
DOI: 10.1145/3269206.3269250
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Parkinson's Disease from Interactions with a Search Engine

Abstract: Parkinson's disease (PD) is a slowly progressing neurodegenerative disease with early manifestation of motor signs. Recently, there has been a growing interest in developing automatic tools that can assess motor function in PD patients. Here we show that mouse tracking data collected during people's interaction with a search engine can be used to distinguish PD patients from similar, non-diseased users and present a methodology developed for the diagnosis of PD from these data.A main challenge we address is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The remaining 42 articles focus on analysis at the organizational level. There is a clear emphasis on qualitative case study analysis (38 articles) as opposed to quantitative analysis (9 articles - Gu et al, 2019;Jimmy et al 2019;Allerhand et al, 2018;Lagrosen, 2018;Yan et al, 2016;Sun, Huang and Chu, 2015;Koeling, Tate and Carroll, 2011;Emerencia et al, 2011 Farouk, Richardson andSanthapparaj, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The remaining 42 articles focus on analysis at the organizational level. There is a clear emphasis on qualitative case study analysis (38 articles) as opposed to quantitative analysis (9 articles - Gu et al, 2019;Jimmy et al 2019;Allerhand et al, 2018;Lagrosen, 2018;Yan et al, 2016;Sun, Huang and Chu, 2015;Koeling, Tate and Carroll, 2011;Emerencia et al, 2011 Farouk, Richardson andSanthapparaj, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Another instance is mouse movement data extraction. Recent studies have shown how mouse movement tracking can assess motor function for the prediction of Parkinson's disease (Allerhand et al 2018;Ryen, Doraiswamy and Horvitz 2018). The tech firm that extracts this information is under no obligation to inform the individual if mouse movement jitters are consistent with Parkinson's; instead the data is likely to be sold to the individual's health insurer who might increase premiums or cut off coverage altogether (McNamee 2019).…”
Section: A More Insidious Scenario Of Surveillance Capitalism -Unethical Target Marketingmentioning
confidence: 99%
“…For example, past work analyzed search logs of large populations to understand seasonal patterns of information seeking for mental health issues (Ayers et al, 2013), to quantify the effect of news reporting on suicidal ideation (Yom-Tov and Fischer, 2017), to study the needs of people during the COVID19 pandemic (Suh et al, 2021), and to estimate the anxiety of search engine users (Youngmann and Yom-Tov, 2018). As a screening tool, search engine data was leveraged for screening of lung carcinoma (R. W. White and Horvitz, 2017), neurodegenerative disorders (Allerhand et al, 2018;R. White et al, 2018;Youngmann et al, 2019), diabetes (Hochberg et al, 2019), stroke (Shaklai et al, 2021), eating disorders (Sadeh-Sharvit et al, 2020), and solid-tumor cancers (Yom-Tov, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As a screening tool, search engine data was leveraged for screening of lung carcinoma (R. W. White and Horvitz, 2017), neurodegenerative disorders (Allerhand et al, 2018; R. White et al, 2018; Youngmann et al, 2019), diabetes (Hochberg et al, 2019), stroke (Shaklai et al, 2021), eating disorders (Sadeh-Sharvit et al, 2020), and solid-tumor cancers (Yom-Tov, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation